Role of Education System in Shaping Social Values in Nepal - Paudel, Ganesh Prasad (Devkota Journal of Interdisciplinary Studies, 2026)
This article examines the role of the education system in shaping social values in Nepal through documentary analysis. It reviews the historical development of Nepali education from the Panchayati regime to the present federal democratic republic and analyzes how shifting political ideologies have shaped educational goals, curricula, and value formation. It also discusses how critical pedagogy empower minorities challenging oppressive social values and practices. Findings indicate that the Panchayati education system centralized the socio-cultural values of the ruling elite class whereas post-1990 democratic reforms emphasized inclusiveness, diversity, human rights, and democratic values. National education policies, curriculum frameworks, and higher education programs increasingly foreground social values, civic consciousness, and life skills. The article concludes that integrating critical pedagogy within the Nepali education system can promote social justice, pluralism, and inclusive national development. Thus, this study attempts to expose the vital role of education system in the formation of social values and civic consciousness so that it helps to reform current education policies and practices.